Management of Unruptured Intracranial Aneurysm - พันธุ์พฤทธิ์ พงศ์พัฒน์; ศรีอมรรัตนกุล กิติพร; อัครธรรมโชติ นาแสง (Thai Journal of Neurological Surgery, 2025)
At present, unruptured intracranial aneurysms (UIA) are more detectable but no standard treatment guideline has been established. If we know the pathophysiology, natural history of UIA, and risk factors that influence management outcomes, we will be able to provide the proper management.